Environmental sustainability in the wine industry, a literature review - Giulia Alessandri; Tiberio Daddi; Fabio Iraldo (Cleaner Production Letters)
The issue of sustainable food production has become increasingly important in recent years, starting from Sustainable Development Goals in 2015, moving through important events like Farm to Fork strategy up until the United Nations Food System Summit in 2021. The wine industry also, as a niche of the agri-food sector, has been influenced by this change, but despite its economic and cultural value, its sustainability issues have not been sufficiently explored by academia. The present research expands the debate on environmental sustainability in the wine industry by observing how management academia has addressed this topic over the last twelve years, defining the state of the art of a quite new and unexplored topic. The research has been structured as a systematic literature review of academic papers from 2009 till the first half of 2022. This methodology provides a clear overview of sustainable management practices, effective and potential, throughout the entire agri-food wine production process.The papers identified are categorized and divided into major (most recurrent) and secondary topics, according to the prevalence criterion.The findings and discussion section provides an in-depth description and analysis of each category, as well as research gaps identification and possible academic issues. Since it was not possible to find similar works, this research would like to be seen as an opportunity to develop the research on environmental sustainability in the wine industry and align the interest of academia and wine stakeholders defining the path for future research.